
How do you factor #a^2 - 2ab +b^2# - Socratic
2018年3月4日 · (a - b)^2 Break down the expression into a simpler form by regrouping and putting brackets. a^2 - 2ab +b^2 a^2 - ab - ab +b^2 a(a - b) - b(a - b) (a - b) (a - b) (a - b)^2
Why does (A+B)^2 = A^2+2AB+B^2 not work for matrices?
2018年2月19日 · Why does #(A+B)^2 = A^2+2AB+B^2# not work for matrices? Precalculus. 1 Answer George C. Feb 19, 2018 ...
How do you factor a^2 + b^2? - Socratic
2015年5月15日 · Whereas a^2-b^2 = (a+b)(a-b) is very simple, to factor a^2+b^2 requires the use of complex numbers. If i = sqrt(-1) then (a+ib)(a-ib) =a^2+iab-iab-i^2b = a-i^2b = a^2-(-1)b^2 = …
If (a^2-b^2)sintheta + 2ab costheta = a^2+b^2, then what
2016年11月27日 · If #(a^2-b^2)sintheta + 2ab costheta = a^2+b^2#, then what will the value of #sintheta# be? Trigonometry Trigonometric Identities and Equations Proving Identities 2 Answers
Classifying reactions? - Socratic
2018年2月24日 · Endothermic Exothermic Endothermic Endothermic Exothermic The stronger the bond, the more the energy required to break it, similarly the stronger the bond formed, the …
How do you solve x^2(a^2+2ab+b^2) = x(a+b) by factoring?
2015年8月21日 · First, notice that you can write #(a^2 + 2ab + b^2)# as the square of #(a + b)#. #a^2 + 2ab + b^2 = (a + b)^2# ...
If a^2 + b^2 = 4 and (a-b)^2 =2, what is the value of ab? - Socratic
2018年3月30日 · It follows that a^2 + b^2 = 2 + 2ab, and since we're given that a^2+ b^2 = 4, we can say 4 = 2 + 2ab. Doing a little algebra we get 4 = 2(1 + ab) 2 = 1 + ab ab = 1 Hopefully this …
How do you factor #a² + 2ab + b² - x² - 6x - 9#? - Socratic
2016年5月20日 · (a+b+x+3)(a+b-x-3). Use A^2-B^3=(A+B)(A-B) The expression is (a+b)^2-(x+3)^2 (a+b+x+3)(a+b-x-3). How do you find the two numbers by using the factoring method, …
Show that if A and B are square matrices such that - Socratic
2018年3月4日 · #=A^2+2AB+B^2#, as desired! Answer link. Related questions. How do I determine the molecular shape of a ...
In matrix multiplication, is (A-B)(A+B) = A^2-B^2? - Socratic
2015年7月9日 · No, because matrix multiplication is not commutative in general, so (A-B)(A+B) = A^2+AB-BA+B^2 is not always equal to A^2-B^2 Since matrix multiplication is not …